Bis(2-{[2,8-bis(trifluoromethyl)quinolin-4-yl](hydroxy)methyl}piperi din-1-ium) tetrachloridodiphenylstannate(IV) - Wardell, J.L.; Wardell, S.M.S.V.; Tiekink, E.R.T.; de Lima, G.M. (International Union of Crystallography, 2010)
In the title salt, (C17H17F6N2O)(2)[Sn(C6H5)(2)Cl-4], the complete anion is generated by crystallograaphic inversion symmetry, giving a trans-SnC2Cl4 octahedral coordination geometry for the metal atom. In the cation, the quinoline residue is almost normal to the other atoms, so that the ion has an L-shaped conformation [the C-C-C-C torsion angle linking the fused-ring systems is 100.9 (7)degrees]; the six-membered piperidin-1-ium ring has a chair conformation. An intramolecular N-H center dot center dot center dot O interaction occurs. In the crystal, N-H center dot center dot center dot Cl and O-H center dot center dot center dot Cl hydrogen bonds link the components into a supra-molecular chain propagating along the a axis. C-H center dot center dot center dot Cl interactions are also present.